1991
DOI: 10.1002/jso.2930480307
|View full text |Cite
|
Sign up to set email alerts
|

Heating efficiency of radiofrequency capacitive hyperthermia for treatment of deep‐seated tumors in the peritoneal cavity

Abstract: We analyzed heating profiles from 318 hyperthermic treatments of 39 patients with recurrent or inoperable cancers of the digestive organs whose deep-seated tumors were treated by radiofrequency (RF) capacitive heating of the abdominal region, and we investigated the heating efficiency and antitumor effect of such treatment. It was apparent that heating with a mean maximum RF output of 1,000 watts (700 watts at least), repeated four times or more, was necessary for a high rate of response by the tumor. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 7 publications
0
18
0
2
Order By: Relevance
“…28 -30 With hyperthermia treatment between 43°C and 45°C, the tissue temperature being moderately raised for a certain period of time is expected to induce cell death by affecting membrane fluidity and the cytoskeletal, protein and nuclear structures, and also disrupting DNA replication. 31 Several reports have revealed that osteonecrosis can be induced by RF. 12 -16 The idea of combining freezing and heating was first proposed by Gage et al 17 in 1982.…”
Section: Discussionmentioning
confidence: 99%
“…28 -30 With hyperthermia treatment between 43°C and 45°C, the tissue temperature being moderately raised for a certain period of time is expected to induce cell death by affecting membrane fluidity and the cytoskeletal, protein and nuclear structures, and also disrupting DNA replication. 31 Several reports have revealed that osteonecrosis can be induced by RF. 12 -16 The idea of combining freezing and heating was first proposed by Gage et al 17 in 1982.…”
Section: Discussionmentioning
confidence: 99%
“…Опухолевые клетки по сравнению с нор-мальными более чувствительны к теплу, поэтому такое воздействие приводит к необратимому разрушению опухоли, происходит полная резекция опухолевого образования размером 3-5 см (рис. 9) [41].…”
Section: рис 6 реконструкция молочной железы после мастэктомииunclassified
“…A radiofrequency probe (15-gauge) with RFA electrodes is inserted in the tumor, and an alternating high-frequency electric current (400 -500 kHz) is administered. The heat that is generated affects the cell membrane's fluidity and the cytoskeleton proteins and finally acts on the nuclear structure, resulting in the interruption of cell repli- cation [22]. This finally leads to irreversible tumor destruction, as tumor cells are more susceptible to heat than are normal cells.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%